FOSTERING TEACHER CREATIVITY THROUGH DIGITAL LEADERSHIP, COLLABORATIVE PRACTICES, AND WORK MOTIVATION - Lastrioza; Anisah; Jasrial; Merika Setiawati; Zukhria (Curricula: Journal of Teaching and Learning, 2026)
This study aims to analyze the influence of digital leadership, teamwork, and work motivation on teacher creativity at State Senior High Schools in West Pasaman Regency. The research employs a quantitative approach using a causal-associative correlational design. The research sample consists of 195 teachers across State Senior High Schools in West Pasaman Regency, selected through the Stratified Proportional Random Sampling technique. Data were systematically collected using a structured questionnaire and analyzed using path analysis. The results show that digital leadership has a direct and significant influence on teacher creativity, albeit with a relatively small contribution of 1.7%. Meanwhile, teamwork proves to be the most dominant factor influencing teacher creativity, contributing 62.1%. Work motivation also exerts a strong direct influence on teacher creativity, with a contribution of 19.1%. Conversely, the data analysis reveals no direct influence of digital leadership on teamwork, nor an indirect influence of digital leadership on teacher creativity through work motivation. However, a significant indirect influence exists between teamwork and teacher creativity as mediated by work motivation, contributing 16.6%. Overall, these empirical findings confirm that teamwork is the most decisive factor in enhancing teacher creativity in the school environment, operating both directly and indirectly through work motivation. Therefore, strengthening a collaborative climate among educators should be prioritized as the key strategy to optimize instructional creativity.